The Relationship Between Physical Fitness and Sports Motivation of 13-15 Year Olds in the Sport of Football - Kusumah, Rangga; Saputra, Moch. Yamin; Syahid, Angga M. (Journal of Physical Education Innovation, 2025)
Physical fitness is the ability to perform activities without excessive fatigue. Physical fitness is achieved because of the encouragement or stimulation in the form of sports motivation. This study aims to determine the relationship between physical fitness and sports motivation in the sport of soccer aged 13-15, because at this age there are psychological and physical changes in the body. The instruments in this study used the Physical Fitness Test (TKJI) to measure the level of physical fitness and the Sport Motivation Scale (SMS) questionnaire to determine the sports motivation of the players with a sample population of PS BRT Subang academy players. Data analysis used the Shapiro-Wilk test, Levene Statistic, and Pearson Correlations with the help of the SPSS 29 application. Based on data processing and analysis, it can be found that there is a significant relationship between the relationship between physical fitness and sports motivation aged 13-15 years in the sport of soccer with a value The significance shows a value of 0.026 < 0.05 . High sports motivation also has high fitness. impact on control in performing physical exercises.